Ascorbic acid prevents oxidative stress in glutathione-deficient mice: effects on lung type 2 cell lamellar bodies, lung surfactant, and skeletal muscle. - Jain, A (1992)
Glutathione deficiency in adult mice leads to lung type 2 cell lamellar body and mitochondrial damage; as reported here, these effects are associated with marked decrease of the levels of phosphatidylcholine (the main component of lung surfactant) in the lung and the bronchoalveolar lining fluid. Severe mitochondrial damage was also found in skeletal muscle. Treatment with ascorbate (1-2 mmol per kg of body weight per day), which led to greatly increased (approximately 2-fold) levels of lung and muscle mitochondrial glutathione, prevented damage to lamellar bodies and mitochondria as well as the decline of phosphatidylcholine levels in lung and alveolar lining fluid. The findings indicate that glutathione deficiency leads to depletion of lung surfactant and that this can be prevented with ascorbate. Administration of ascorbate spares glutathione and prevents cellular damage. Lamellar body degeneration in glutathione deficiency appears to be associated with oxidative damage to the perilamellar membrane, which contains the enzymes required for phosphatidylcholine synthesis. It is notable that although severe glutathione deficiency is lethal to newborn rats, which apparently do not synthesize ascorbate, adult mice are better able to survive such a deficiency because they can synthesize ascorbate. The present studies, which suggest that high doses of ascorbate may be of therapeutic value, emphasize that ascorbate and glutathione have actions in common and that they function together in a physiologically significant antioxidant system.